Dynamics Dakwah Social Tuan Guru in Improving the Religion of the Religious People in the Lombok Community - Udin, Udin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2020)
In this research, the writer examines the social dynamics of the teachings of Tuan Guru in enhancing religious harmony in the Lombok community. This study also tries to reveal the existence of the Tuan Guru in terms of da'wah, social aspects, preservation of cultural traditions and religious patterns of the Lombok people. This study found that Tuan Guru in Lombok has a very broad position and role, not only in religious aspects, but also in the social, economic and political fields. With the capacity in his possession Tuan Guru gives a social propaganda about the importance of religious harmony, the propaganda is not only done in society but through educational institutions as well as boarding schools